Hypermedia in 15 minutes : how can hypermedia help me? (O'Reilly, 2017)
"In this short video, Mike Amundsen reviews the history and power of the Web's hypermedia links and forms before explaining how API service providers and client app developers can take advantage of hypermedia to create better, more available, and more resilient applications for the internet."--Resource description page